2021
DOI: 10.3389/fphys.2021.641310
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Right Ventricle Structure and Function in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a disease resulting in increased right ventricular (RV) afterload and RV remodeling. PAH results in altered RV structure and function at different scales from organ-level hemodynamics to tissue-level biomechanical properties, fiber-level architecture, and cardiomyocyte-level contractility. Biomechanical analysis of RV pathophysiology has drawn significant attention over the past years and recent work has found a close link between RV biomechanics and physiological funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 107 publications
(266 reference statements)
0
26
0
Order By: Relevance
“…PAH is a complex, progressive vascular disease clinically defined as a maladaptive increase in pulmonary arterial pressure in the absence of elevated left heart pressure [3,4,15]. In response to PAH, the RV undergoes structural and functional remodeling, including RV hypertrophy, which is a key determinant of long-term PAH outcomes and is associated with an increased risk of heart failure as well as sudden death [12,15]. However, most previous studies have concentrated predominantly on the impact of biomechanical forces such as shear stress on the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PAH is a complex, progressive vascular disease clinically defined as a maladaptive increase in pulmonary arterial pressure in the absence of elevated left heart pressure [3,4,15]. In response to PAH, the RV undergoes structural and functional remodeling, including RV hypertrophy, which is a key determinant of long-term PAH outcomes and is associated with an increased risk of heart failure as well as sudden death [12,15]. However, most previous studies have concentrated predominantly on the impact of biomechanical forces such as shear stress on the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Nour et al suggested that intrapulmonary shear stressmediated endothelial function enhancement could provide an effective target for PAH treatment [17]. Notably, the key determinant of mortality and morbidity of patients with PAH is the consequence of RV dysfunction [15], but the molecular mechanisms driving RV decompensation in the process of PAH remain largely unknown. Hereby, starting from a clinical observation, we found that despite an increasing expression of circulating miR-21 in patients with PAH, there was a significant drop in circulating miR-21 expression along with RV dysfunction among patients who were hospitalized for decompensated HF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various known factors that compromise pulmonary endothelial function also lead to progressive remodeling of the pulmonary arteries and/or veins, and together, leads to elevated pulmonary arterial pressure (>25 mmHg at rest), as well as increased afterload in the right ventricle (RV) (Thenappan et al, 2018). Initially, the increased work imposed on the RV to maintain right heart output stimulates RV hypertrophy (adaptive phase) but becomes maladaptive with RV dilatation, increasing myocardial energetic demand, thereby, resulting in greatly elevated risk of death (Vonk Noordegraaf et al, 2017;Sharifi Kia et al, 2021). Activation of the sympathetic nervous system, endothelin-1, and adrenal production of catecholamines is considered to be important both for the early compensatory increase in RV contractility and in subsequent RV dysfunction and remodeling in the long term (De Man et al, 2013;Vaillancourt et al, 2017;Cassady and Ramani, 2020;Prisco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%